2021
DOI: 10.1089/ars.2021.0027
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Endothelial Dysfunction in Sepsis and Acute Inflammation

Abstract: Significance: Under homeostatic conditions, the endothelium dynamically regulates vascular barrier function, coagulation pathways, leukocyte adhesion, and vasomotor tone. During sepsis and acute inflammation, endothelial cells (ECs) undergo multiple phenotypic and functional modifications that are initially adaptive but eventually become harmful, leading to microvascular dysfunction and multiorgan failure. Critical Issues and Recent Advances: Sepsis unbalances the redox homeostasis toward a pro-oxidant state, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 169 publications
(156 reference statements)
2
93
0
Order By: Relevance
“…There is evidence that redox homeostasis is disrupted in sepsis resulting in oxidative stress, which together with excessive inflammation is thought to cause mitochondrial, endothelial and microvascular dysfunction, resulting in vasoplegia, inflammation-mediated tissue injury, tissue hypoxia and multi-organ dysfunction (Joffre & Hellman, 2021) (Lankadeva, Okazaki, Evans, Bellomo & May, 2019).…”
Section: Pathophysiology Of Sepsis-induced Cardiovascular and Renal Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that redox homeostasis is disrupted in sepsis resulting in oxidative stress, which together with excessive inflammation is thought to cause mitochondrial, endothelial and microvascular dysfunction, resulting in vasoplegia, inflammation-mediated tissue injury, tissue hypoxia and multi-organ dysfunction (Joffre & Hellman, 2021) (Lankadeva, Okazaki, Evans, Bellomo & May, 2019).…”
Section: Pathophysiology Of Sepsis-induced Cardiovascular and Renal Dysfunctionmentioning
confidence: 99%
“…The factors causing sepsis‐induced organ dysfunction remain unclear due to the complex pathophysiology of sepsis that changes as the response to the infection progresses. There is evidence that redox homeostasis is disrupted in sepsis resulting in oxidative stress, which together with excessive inflammation is thought to cause mitochondrial, endothelial and microvascular dysfunction, resulting in vasoplegia, inflammation‐mediated tissue injury, tissue hypoxia and multi‐organ dysfunction (Joffre & Hellman, 2021; Lankadeva et al, 2019) (Figure 1).…”
Section: Pathophysiology Of Sepsis‐induced Cardiovascular and Renal Dysfunctionmentioning
confidence: 99%
“…Oxidative stress due to H 2 O 2 exposure causes extensive cytoskeletal disruption to endothelial cells leading to significant endothelial retraction and microangiopathic dysfunction[ 22 ]. The net effect of microvascular H 2 O 2 exposure is microangiopathic dysfunction, impaired vasomotor responsiveness, barrier disruption with edema formation, and irreversible hypotension (septic shock)[ 22 , 77 ]. Studies have reported hypotension in an animal model after intravenous administration of H 2 O 2 [ 25 ].…”
Section: Clinical Manifestations Of H2o2 Induced Oxidative Stressmentioning
confidence: 99%
“…On a more fundamental level, the endothelium is critically involved in preventing inappropriate coagulation by maintaining barrier function and producing several endogenous anticoagulants[ 101 ]. The elevated levels of blood H 2 O 2 reported in sepsis can permeate endothelial cells throughout the body causing substantial oxidative stress accompanied by profound disruption in both form and function[ 77 , 102 ]. Studies have reported significant endothelial dysfunction that is associated with mortality and severity of coagulopathy[ 101 ].…”
Section: Clinical Manifestations Of H2o2 Induced Oxidative Stressmentioning
confidence: 99%
“…Nuclear elements released from NETs affect neighboring cells, promoting endothelial cell necrosis and apoptosis and, hence, increasing the release of more nuclear content to the bloodstream via a second pathway which, in the end, leads to a positive feedback process that establishes a correlation between the increase in the release of nuclear content and disease progression. Given the tight relationship that exists between the production of free radicals and the generation of oxidative stress resulting from endothelial cell dysfunction, especially in the context of sepsis progression, focusing on the molecular features of nuclear elements released to the bloodstream is a source of substantial potential clinical interest [ 2 ]. Nuclear factors typically found in the bloodstream of sepsis patients include free DNA, mono-, di-, and oligo-nucleosomes, and free histone proteins, among other chromatin-derived elements; thus, these factors are acquiring increasing relevance as DAMPs.…”
Section: Introductionmentioning
confidence: 99%